A coastal surface seawater analyzer for nitrogenous nutrient mapping. (1st November 2017) - Masserini, Robert T.; Fanning, Kent A.; Hendrix, Steven A.; Kleiman, Brittany M.
Abstract: Satellite-data-based modeling of chlorophyll indicates that ocean waters in the mesosphere category are responsible for the majority of oceanic net primary productivity. Coastal waters, which frequently have surface chlorophyll values in the mesosphere range and have strong horizontal chlorophyll gradients and large temporal variations. Thus programs of detailed coastal nutrient surveys are essential to the study of the dynamics of oceanic net primary productivity, along with land use impacts on estuarine and coastal ecosystems. The degree of variability in these regions necessitates flexible instrumentation capable of near real-time analysis to detect and monitor analytes of interest. This work describes the development of a portable coastal surface seawater analyzer for nutrient mapping that can simultaneously elucidate with high resolution the distribution of nitrate, nitrite, and ammonium - the three principal nitrogenous inorganic nutrients in coastal systems. The approach focuses on the use of pulsed xenon flash lamps to construct an analyzer which can be adapted to any automated chemistry with fluorescence detection. The system has two heaters, on-the-fly standardization, on-board data logging, an independent 24 volt direct current power supply, internal local operating network, a 12 channel peristaltic pump, four rotary injection/selection valves, and an intuitive graphical user interface. Using the methodology of Masserini and Fanning (2000) the detection limits for ammonium, nitrite, and nitrate plus nitrite were 11, 10, and 22 nM, respectively. A field test of the analyzer in Gulf of Mexico coastal waters demonstrated its ability to monitor and delineate the complexity of inorganic nitrogen nutrient enrichments within a coastal system. Highlights: A fluorescence based analyzer capable of near real-time mapping of nitrogenous nutrients was developed. The analyzer is portable and easily adapted to other fluorescent chemistries. Nanomolar nitrate, nitrite, and ammonium concentrations can be quantified in coastal waters.